2015
DOI: 10.1016/j.polymdegradstab.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of common agrichemicals on the environmental stability of polyethylene films

Abstract: The impact of commonly used agrichemicals (Paraquat, Mancozeb, Chlorpyrifos and Sulfur) on the environmental stability of polyethylene films has been evaluated under accelerated photo-oxidative conditions. Paraquat and Mancozeb when applied to unstabilized clear polyethylene film, followed by exposure to UV radiation, resulted in direct attack of the polymer, evident by faster rates of oxidation and shorter times to embrittlement compared to a polyethylene control. Reapplication of these chemicals during ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It is commonly used in the melt extrusion process, which produces one of the most popular packaging materials. LDPE has a low density and excellent mechanical properties, as well as excellent stress cracking and rigidity, as well as good heat resistance and chemical stability (Kumar et al, 2020;Yeh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly used in the melt extrusion process, which produces one of the most popular packaging materials. LDPE has a low density and excellent mechanical properties, as well as excellent stress cracking and rigidity, as well as good heat resistance and chemical stability (Kumar et al, 2020;Yeh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation degrees of these films were calculated according to the equations for carbonyl index (C.I. ): 44 For LDH particles with poorer dispersity (0 min in acetone), the C.I. value after thermal treatment was measured as 0.3107 (Table S3, ESI†).…”
mentioning
confidence: 99%
“…The oxidation degrees of these films were calculated according to the equations for carbonyl index (C.I. ): 44 C:I: ¼ absorbance at1716 cm À1 absorbance at 1460 cm À1 :…”
mentioning
confidence: 99%
“…In a recent study, Yeh et al [2015] showed that PE film embrittlment time was retarded by 7 days when sprayed with sulphur containing agrochemical (29 days) compared to no treatment (22 days), under accelerated UV ageing. Our results are therefore in agreement with some of the literature findings, where sulphur compounds had a retarding effect on PE photo-degradation, as they can behave as antioxidants by decomposing hydroperoxide.…”
Section: Influence Of Ph On Pe Photo-degradationmentioning
confidence: 99%
“…The service lifetime of polymer films is controlled by the chemical reactions leading to chain scission and mediating environmental factors. The rate of PE film degradation depends on several factors such as, but not limited to, the type and concentration of pro-degradant, UV exposure, temperature, rain, humidity conditions, geographical location [Kockott, 1989, Sampers, 2002, Kaczmarek et al, 2005, Basfar and Ali, 2006, Briassoulis, 2007, season [Gijsman and Sampers, 1998, Sampers, 2002, Briassoulis, 2007, pesticides and herbicides [Espi et al, 2007, Yeh et al, 2015, and other external environmental factors [Kockott, 1989, Sampers, 2002. All these factors may interact in synergy or antagonistically [Corti et al, 2010], which increases the difficulty in predicting polymer lifetime.…”
Section: Introductionmentioning
confidence: 99%